SYNE1-related autosomal recessive cerebellar ataxia, congenital cerebellar hypoplasia, and cognitive impairment - Lauren Swan; John Cardinal; David Coman (Clinics and Practice, 2018)
The SYNE1 (spectrin repeat-containing nuclear envelope protein 1) gene encodes a family of spectrin structural proteins that are associated with anchoring the plasma membrane to the actin cytoskeleton. SYNE1-related disease is most commonly reported in autosomal recessive spinocerebellar ataxia 8, which demonstrates variable age of onset with a median of 30 years of age. However pathogenic mutations in SYNE1 are also causative of arthrogryposis multiplex congenital, a severe congenital neuromuscular condition. Here in we report monozygous twins with childhood onset ataxia, cerebellar hypoplasia, dysarthria, and cognitive impairment sharing two novel heterozygous mutations in the SYNE1 gene. Our family may expand the clinical phenotype associated with SYNE1-related disease and offers possible genotype-phenotype correlations of a rare continuum of clinical disease phenotypes from neonatal to adult onset.